2017
DOI: 10.1177/0300985816684929
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Frog Virus 3 (Ranavirus, Iridoviridae) Infection in Wood Frogs (Rana sylvatica)

Abstract: Wood frogs ( Rana sylvatica) are highly susceptible to infection with Frog virus 3 (FV3, Ranavirus, Iridoviridae), a cause of mass mortality in wild populations. To elucidate the pathogenesis of FV3 infection in wood frogs, 40 wild-caught adults were acclimated to captivity, inoculated orally with a fatal dose of 10 pfu/frog, and euthanized at 0.25, 0.5, 1, 2, 4, 9, and 14 days postinfection (dpi). Mild lesions occurred sporadically in the skin (petechiae) and bone marrow (necrosis) during the first 2 dpi. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…While the majority of X. laevis -FV3 research has bypassed the skin barrier via intraperitoneal injection of virus into the host (18, 227229), water-bath exposure of healthy tadpole and adult X. laevis to FV3-infected frogs in the same tank revealed that healthy individuals become infected with FV3 within 3 h of exposure (230). A key symptom of FV3 infection in susceptible developmental stages or frog species is the formation of skin lesions, skin shedding, and epidermal cell necrosis (231, 232). It is proposed that loss of the skin barrier during FV3 infection allows for increased pathogen entry and ultimately leads to mortality in susceptible hosts, stressing the overall importance of the skin barrier and barrier integrity.…”
Section: Impact Of Environment On Host Barriersmentioning
confidence: 99%
“…While the majority of X. laevis -FV3 research has bypassed the skin barrier via intraperitoneal injection of virus into the host (18, 227229), water-bath exposure of healthy tadpole and adult X. laevis to FV3-infected frogs in the same tank revealed that healthy individuals become infected with FV3 within 3 h of exposure (230). A key symptom of FV3 infection in susceptible developmental stages or frog species is the formation of skin lesions, skin shedding, and epidermal cell necrosis (231, 232). It is proposed that loss of the skin barrier during FV3 infection allows for increased pathogen entry and ultimately leads to mortality in susceptible hosts, stressing the overall importance of the skin barrier and barrier integrity.…”
Section: Impact Of Environment On Host Barriersmentioning
confidence: 99%
“…16 Although this is the first report of inclusion bodies in lungs of ranaviral-infected dragons, there are reports of inclusion bodies in keratinocytes adjacent to areas of necrosis in skin lesions of BIV-like infected boreal toads (Anaxyrus boreas boreas), in circulating leukocytes of a FV3-infected eastern box turtle (Terrapene carolina carolina), and in the cytoplasm of skin epidermal cells of FV3infected wood frogs euthanized 14 dpi. 1,13,16 To identify the progression of BIV infection in EWDs at different time points, we collected cloacal swabs and tissue samples for PCR, virus isolation, histopathology, and IHC. In our study, Ranavirus sp DNA was detected in all cloacal swabs, as well as liver and kidney tissue samples collected at the first time point (3 dpi) in the early stages of infection, which contrasts to an FV3 pathogenesis study in wood frogs (Rana sylvatica) where DNA was not detected in multiple tissues until shortly before death.…”
Section: Discussionmentioning
confidence: 85%
“…Inclusion bodies have previously been described in multiple organs of ranavirus-infected fish, tortoises, turtles, and amphibians 1,13,16,17,22,25,29,35 and, up until now, only in the liver of lizards. 8,24 While inclusion bodies are commonly associated with ranaviral infections, 8,17,18 they are not consistently reported.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 In this issue of Veterinary Pathology, Forzán et al, using experimental infections of a Ranavirus, Frog Virus 3 (FV3), in wood frogs (Rana sylvatica), provide a new and wellcharacterized model that advances our understanding of the other major EID in amphibians. 8 The ranaviruses were discovered in the mid-1960s as part of efforts to characterize the herpesvirus-associated renal carcinomas, but for a long time their association with natural disease was limited to American bullfrog (Lithobates catesbeianus) tadpoles with generalized edema and hemorrhagic lesions grossly resembling red leg syndrome. 22 In the 1990s, Ranavirus-associated mass mortality events in native salamanders and frogs from North America 4,9 and common frogs (Rana temporaria) 5 from Europe significantly raised the profile on these viruses.…”
mentioning
confidence: 99%